2010
DOI: 10.1302/0301-620x.92b3.22787
|View full text |Cite
|
Sign up to set email alerts
|

Bone-turnover markers in fracture healing

Abstract: Biochemical markers of bone-turnover have long been used to complement the radiological assessment of patients with metabolic bone disease. Their implementation in daily clinical practice has been helpful in the understanding of the pathogenesis of osteoporosis, the selection of the optimal dose and the understanding of the progression of the onset and resolution of treatment. Since they are derived from both cortical and trabecular bone, they reflect the metabolic activity of the entire skeleton rather than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 47 publications
(135 reference statements)
2
77
3
5
Order By: Relevance
“…All of these serum markers increased or decreased after different skeletal bone fractures and fluctuated during fracture healing in agreement with the literature data (14,(24)(25)(26). For example, OC elevated at 24 weeks after fracture of the tibial shaft and rose at 1 week after distal radial fracture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All of these serum markers increased or decreased after different skeletal bone fractures and fluctuated during fracture healing in agreement with the literature data (14,(24)(25)(26). For example, OC elevated at 24 weeks after fracture of the tibial shaft and rose at 1 week after distal radial fracture.…”
Section: Discussionsupporting
confidence: 90%
“…PYD-DPYD peaks 1 to 8 weeks after proximal femoral fracture, and PYD peaks 1 to 4 weeks after fracture of the tibial shaft. PYD is a less specific marker of bone resorption than DPYD since it is abundant in all connective tissues; however, DPYD is distributed generally in bone and dentin, and 90% of the bone matrix consists of type I collagen (14,26). In the present study, no significant changes were observed for the markers of bone formation and resorption analyzed between the groups.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It also is important to point out that the baseline urine NTX and BALP levels were greater in the fracture group. A previous study showed that fracture healing increased bone marker responses [11]. Thus, it is possible that the pretreatment bone marker levels in the fracture group were already elevated to maximal or submaximal levels, contributing to smaller degrees of change in both bone markers during posttreatment followup.…”
Section: Discussionmentioning
confidence: 92%
“…Therapy with skeletal stem cells from bone marrow proved effective in osteogenic stimulation of fracture nonunion through a noninvasive method, by promoting bone union in patients who had a one-year or longer fracture and in whom several previous surgeries had failed (ZAMPROGNO, 2007). Cox et al (2010) studied bone markers in fracture consolidation, and concluded that the available evidence does not support the routine use of these markers to evaluate fracture healing, and the ability to measure interventions for accelerating fracture consolidation has not been established.…”
Section: Treatmentmentioning
confidence: 99%